Study of risk factors associated with adverse outcome in a severe coronary artery disease (syntax score >22) with different therapeutic strategies - Karnik, Vidur G.; Patil, Yogesh B.; Pai, N.; Bhat, M. N.; Kamath, R. L.; Kamath, P; Bhatt, Rajesh (International Journal of Advances in Medicine, 2019)
Background: The specific question of whether PCI or surgical treatment offers any advantage over MT in patients with stable angina and multivessel disease remains unanswered. Objective of our research was to study various risk factors which interferes the outcome of various therapeutic procedures in coronary artery disease. Methods: This was prospective observational study carried out in a tertiary care center from July 2014 to July 2016. A total of 98 subjects undergoing different therapeutic strategies were followed up. Risk factors which interferes the outcome of various therapeutic procedures in coronary artery disease (CAD) were studied. Results: There was a significant difference in mean SYNTAX score (P = 0.003), urine micro albumin levels (P=0.006), and body mass index (0.046) between those who had MACE and who did not have MACE. Conclusions: The urine micro albumin >30 mg/l and highest SYNTAX score were significantly associated with MACE at 1 year in subject with severe CAD.